Psycho-sociological repercussions on covid-19 patients - Al-Hardan, Zina Saeed Ahmed (Al-Adab Journal, 2022)
Corona virus has a major role in the deterioration of the psychological, state of the injured and occupies a large of the disease, The presence of the injured person for a period of isolation, suffering from what he suffers as a result of his injury, without the presence of anyone with him, leads to a deterioration in the psychological state, and thus a delay in the healing process, there are sufferers who suffer from psychological exhaustion to deal cautiously with everything around them, as well as some of them suffer from their inability to sleep and the great fears of injuring their parents because of them, and life did not return to its normal from, while the social problems lay in the weakness of social relations between the injured and others and their distance from him, which resulted in his feeling of loneliness even more, this unit was divided into two parts, some of whom moved away for preventive precautions, and some of them were accompanied by social stigma, while there were very few citizens, who hid their injury people in order to avoid stigmatization, as for the stigma towards tourists and foreigners, it was much greater after them, the main reason for transmitting the virus to the country.